Ecología trófica de Teius oculatus (Sauria: teiidae) en el sur de la provincia de Córdoba (Argentina): composición, variación anual y estacional de la dieta - Acosta, Juan Carlos (1991)
The aim of this project was to study the composition and the anual variation of the diet of Teius oculatus in Río Cuarto, Córdoba, Argentina, during the summers 1988-1989 and 1989-1990. After the analysis of the stomachs diet categories were established as well as frecuency, volume and the number of individuals consumed. The IRI, relative index of importance, was used to study comparative food data. Our results are: 1) there are basic components (ITA, ACR, COL and LAR) and supplementary ones (ISO, ARA, GRI, FOR, HOM, CAR, IVA and OIT), 2) the species is mainly insectivorous and oportunistic, and 3) the diet varies between and during the seasons depending on food disponibility.